Characterizing the shape of Large Cutting Tools from the Baise Basin (South China) using a 3D geometric morphometric approach. (April 2021) - Li, Hao; Lei, Lei; Li, Dawei; Lotter, Matt G.; Kuman, Kathleen
Highlights: A landmarks-based 3D geometric morphometric approach is applied to LCTs in China. Lateral edges of mesial and basal parts of Baise LCTs are most variable. A tongue-like tip shape is most common and production techniques are consistent. Tip shape consistency may reflect a special functional adaptation. Abstract: The ever-growing use of the landmarks-based 3D geometric morphometric approach in Paleolithic studies is providing researchers with robust datasets that facilitate the interpretation of new research questions that cannot be explored using traditional planform measurements. Here, we utilize this method to investigate the shape of the Large Cutting Tools (LCTs) from the Baise (or Bose) Basin in South China that are heavily debated as Acheulean or Acheulean-like. Our results show that the greatest variability in shape is primarily concentrated along the lateral edges of the mesial and basal parts of the LCTs, which is in contrast with the relative consistency in shape for the distal tips. This trend in shape variability is very likely related to certain functional needs driving the technological investment within different portions of the LCTs during the shaping process (i.e., more extensive shaping in the tips relative to the other remaining parts). Another key feature for LCT tip morphology is the general preference for arched or tongue-like shapes, although some variability still exists. We suggest that the consistency in these tip morphologies likely reflects an inherent mental template in the minds of the LCT makers, and is also probably a specific functional adaptation (e.g., wood working) within the local humid subtropical paleoenvironment. This study provides an important case study demonstrating the successful application of a landmarks-based 3D geometric approach to Asian LCTs, showcasing its innovative potential when investigating the evolution of Paleolithic assemblages.